2004
DOI: 10.1080/02713680490504614
|View full text |Cite
|
Sign up to set email alerts
|

Amino acid prodrugs of acyclovir as possible antiviral agents against ocular HSV-1 infections: Interactions with the neutral and cationic amino acid transporter on the corneal epithelium

Abstract: Analyses of the inhibition pattern of EACV transport suggests the involvement of a single transport system; namely, B(0,+). Design of amino acid prodrugs seems to be an attractive strategy to enhance the solubility of the otherwise poorly aqueous soluble compounds and also to afford a targeted and possibly enhanced delivery of the active drug.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
49
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 19 publications
2
49
2
Order By: Relevance
“…These compounds were designed to target the transporters on the cornea and intestinal epithelial cells for improved ocular and oral absorption of acyclovir, respectively. Previous results indicated that the amino acid ester prodrugs of ACV exhibited affinity toward the amino acid transporters, and the uptake of these prodrugs was efficiently mediated by ASCT1 and B 0,+ (Anand et al, 2004b;Katragadda et al, 2008). In this report, we describe pharmacokinetics of these prodrugs after oral administration in Sprague-Dawley rats.…”
Section: Mediated Intestinal Translocationmentioning
confidence: 96%
See 4 more Smart Citations
“…These compounds were designed to target the transporters on the cornea and intestinal epithelial cells for improved ocular and oral absorption of acyclovir, respectively. Previous results indicated that the amino acid ester prodrugs of ACV exhibited affinity toward the amino acid transporters, and the uptake of these prodrugs was efficiently mediated by ASCT1 and B 0,+ (Anand et al, 2004b;Katragadda et al, 2008). In this report, we describe pharmacokinetics of these prodrugs after oral administration in Sprague-Dawley rats.…”
Section: Mediated Intestinal Translocationmentioning
confidence: 96%
“…A series of novel water-soluble amino acid ester prodrugs of acyclovir were synthesized previously (Anand et al, 2004b;Katragadda et al, 2008). These compounds were designed to target the transporters on the cornea and intestinal epithelial cells for improved ocular and oral absorption of acyclovir, respectively.…”
Section: Mediated Intestinal Translocationmentioning
confidence: 99%
See 3 more Smart Citations